2014
DOI: 10.1117/1.oe.53.7.075108
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of parameters for bonnet polishing based on the minimum residual error method

Abstract: For extremely high accuracy optical elements, the residual error induced by the superposition of the tool influence function cannot be ignored and leads to medium-high frequency errors. Even though the continuous computer-controlled optical surfacing process is better than the discrete one, which can decrease this error to a certain degree, the error still exists in scanning directions when adopting the raster path. The purpose of this paper is to optimize the parameters used in bonnet polishing to restrain th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
6
2
1
Order By: Relevance
“…12, the influences of parameters on the RMSr is that, the larger the TIF diameter is, the smaller the path spacing is and the smaller the RMSr is, otherwise the path types in descending order of impact are as follows: raster path, circle path, and random path. The influence of TIF diameter and path spacing on the ripples is similar to the previous research results [13].…”
Section: Influence Of Process Parameter Combination On Psdcsupporting
confidence: 90%
See 1 more Smart Citation
“…12, the influences of parameters on the RMSr is that, the larger the TIF diameter is, the smaller the path spacing is and the smaller the RMSr is, otherwise the path types in descending order of impact are as follows: raster path, circle path, and random path. The influence of TIF diameter and path spacing on the ripples is similar to the previous research results [13].…”
Section: Influence Of Process Parameter Combination On Psdcsupporting
confidence: 90%
“…Pohl et al [12] observed the simulation of the mid-spatial frequencies generation during the grinding process of optical components. Wang et al [13][14][15] analyzed the optimization of parameters for bonnet polishing based on the minimum residual error method. In addition, a maze path was proposed, which can increase randomness while ensuring uniform trajectory distribution, and avoid periodic surface error.…”
Section: Introductionmentioning
confidence: 99%
“…The VRR's variation with respect to the dwell time and offset of th is demonstrated in Figure 5. It was found that the SR bonnet has a hi PR bonnet under the same polishing conditions, which coincides with ishing BK7 optical glasses reported in [41,44]. However, it was noted ment is not proportional to the increase of the dwell time, as shown in F of both of the two bonnet tools gradually decrease with the increase converge to a constant value, which is quite different from the results When the dwell time is short, the peaks on the surface are easier to eff smoothen, leading to a high material removal rate.…”
Section: Materials Removal Rate Analysissupporting
confidence: 84%
“…However, it was noted that the VRR increment is not proportional to the increase of the dwell time, as shown in Figure 5a. The VRRs of both of the two bonnet tools gradually decrease with the increase in dwell time and converge to a constant value, which is quite different from the results reported in [41,44]. When the dwell time is short, the peaks on the surface are easier to effectively remove or smoothen, leading to a high material removal rate.…”
Section: Materials Removal Rate Analysiscontrasting
confidence: 75%
“…They proposed three kinds of TIFs (sTIFt, sTIFd, and sTIFc). Wang et al 24 also studied the influence of the process parameters on the residual error after polishing. Raster distance, Z -axis offset, inner pressure, H -axis speed, and precession angle were considered in their study.…”
Section: Introductionmentioning
confidence: 99%